2022 AICCRA Deliverables Quality Assurance Report - Ramírez, Margarita M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report is the result of a quality assessment process carried out for all deliverables reported in MARLO during the 2022 Annual Report. During this exercise, we have identified some adjustments to be done to the metadata inputted by cluster leaders (tagged in red color). At the same time, we have also provided a score based on our compliance with our Open Access policy which was used as part of our internal overall Cluster´s performance assessment process